(untitled) (KYAMC Journal, 2018)
Background: Among communicable and non-communicable diseases, neoplastic diseases are the 6th leading cause of death in Bangladesh. Hospital-based cancer registries in Bangladesh reveal more than 50% of subjects with neoplastic disease (cancer) are estimated to be within 30 to 65 years of age. Objective: To observe imaging findings in patient with rectal carcinoma in terms of no residual disease, post treatment fibrosis, residual disease, loco-regional recurrence and metastasis at surveillance by CT, MR scan. Methodology: CT and MRI scan was performed with standard protocol among 64 subjects (both males, females) over a period of one year at department of Radiology and Imaging, KYAMCH who came for follow up. The study subjects were referred from Department of Oncology of same institution. Result: Among total 64 patients majority were female (54.68%) and rest were male (45.32%) and mean age was 51.38 (± 22.86) years. Most (26.56%) of the patients were in 31-40 years age group. CT scan was performed in 81.25% and MRI in 31.25% patients. No recurrence was observed to surveillance imaging in 18.75% patients. Post treatment fibrosis were seen in 23.43% and locoregional recurrence in 20.31% subjects. Local extension (35.93%), lymphadenopathy (43.75%) and distant metastases (26.56%) were observed. Associated imaging findings other than tumour recurrence or extension were ischaemic colitis (10.93%), perforation (4.68%), rectovesical fistula (3.12%), rectouterine fistula (1.56%) and rectovaginal fistula (6.25%). Other than loco regional extension, distant metastases were observed in liver (14.06%), lung (10.94%), bone (6.25%) and brain (4.68%). Conclusion: This study reveals that during image analysis of patients with rectal carcinoma, radiologists should carefully distinguish post treatment fibrosis from local recurrence, check the locoregional areas, possible sites for metastasis and oncologist should request for screening of chest including lower part of neck at the time imaging of abdomen at follow up. KYAMC Journal Vol. 9, No.-3, October 2018, Page 104-109